Differentiation of bipotential gonads in buffalo foetus: A histomorphological study - SINGH, INDERPREET; BANSAL, NEELAM; UPPAL, VARINDER; ANURADHA, ANURADHA (The Indian Journal of Animal Sciences, 2015)
The present study was conducted on buffalo fetuses during early prenatal life to determine the developmental stages from the gonadal ridge to form bipotential gonads. The present study was conducted on the gonads of buffalo fetuses from 2.5 to 4.2 cm CVRL to determine the development of bipotential gonads from the gonadal ridge. The gonadal ridge appeared as a globular or rectangular thickening on the ventromedial surface of mesonephros at 2.5–3.0 cm CVRL (40–42 days). It was lined by simple cuboidal type of epithelium and contained mesenchymal cells, immature RBC’s, differentiating fibroblasts and primordial germ cells. The formation of indifferent gonad started at 3.5 cm CVRL as paired rounded structures, which were attached to the mesonephros by a thin stalk and were present completely separated from the mesonephros at 4.0 cm CVRL. At 3.5 cm CVRL, these gonads were lined by simple cuboidal type of germinal epithelium with some interspersed PGC’s. The PGC’s and epithelium proliferated and penetrated into the underlying mesenchymal tissue to form primitive sex cords. In the centre of indifferent gonads the blastema was observed at 4 cm CVRL. The blastema had variable shape and prominent nucleus.